Narendra Modi and India's global ambition - Sachdev, Pravin (New Delhi Mohit Publications, 2023)
The Premiership of Narendra Modi began on 26 May 2014 with his swearingin as the prime minister of inida at the Rashtrapati Bhavan. he Became the 14th prime minister of india' succeeding manmohan Singh of the Indian National Congress.
Keywords: Prime Minister; World Politics; Narendra Modi